A Model for Implementing a Sustainability Strategy through HRM Practices. (December 2016) - Buller, Paul F.; McEvoy, Glenn M.
Abstract: There is a rapidly growing interest in the topic of sustainability as it relates to long‐term business performance that optimizes the "triple bottom line": economic, environmental, and social outcomes. This article articulates a multilevel conceptual model for executing a business strategy for sustainability primarily through the design and implementation of human resource management practices. The model builds on open systems theory, the resource based view of the firm, and the concept of line of sight to identify certain key organizational capabilities, group competencies, and individual abilities and other characteristics that combine to drive organizational performance when pursuing a sustainability strategy. The article concludes with a discussion of implications of the model for theory, research, and practice.